2019
DOI: 10.1002/ecs2.2675
|View full text |Cite
|
Sign up to set email alerts
|

The role of understory phenology and productivity in the carbon dynamics of longleaf pine savannas

Abstract: Savanna ecosystems contribute ~30% of global net primary production (NPP), but they vary substantially in composition and function, specifically in the understory, which can result in complex responses to environmental fluctuations. We tested how understory phenology and its contribution to ecosystem productivity within a longleaf pine ecosystem varied at two ends of a soil moisture gradient (mesic and xeric). We used the Normalized Difference Vegetation Index (NDVI) of the understory and ecosystem productivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 100 publications
(226 reference statements)
1
29
0
Order By: Relevance
“…Previous studies have reported the long-term precipitation dynamics of these sites during the study period (2009-2017) [40,42], and showed short-term seasonal annual drought and water stress from June to August [38]. This caused significant day-to-day fluctuations in summer ecosystem productivity (GPP decline and recovery) and changes in summer phenological processes across sites.…”
Section: Response Of Summer Day-to-day Phenological Processmentioning
confidence: 93%
See 3 more Smart Citations
“…Previous studies have reported the long-term precipitation dynamics of these sites during the study period (2009-2017) [40,42], and showed short-term seasonal annual drought and water stress from June to August [38]. This caused significant day-to-day fluctuations in summer ecosystem productivity (GPP decline and recovery) and changes in summer phenological processes across sites.…”
Section: Response Of Summer Day-to-day Phenological Processmentioning
confidence: 93%
“…Prescribed fire and weather events (meteorological drought and flood) affected ecosystem-scale phenological processes and productivity [40,49], especially summer phenology (Table 2; Appendix B, Figure A2) because of the variability of water availability. To develop a more thorough understanding of the phenological patterns of the study sites, we investigated SOS, EOS and LOS patterns and characteristics at an inter-annual scale ( Figure 6; Appendix B, Table A1 and Figure A2).…”
Section: Ecosystem-scale Phenological Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Prescribed fire objectives necessitate a detailed and nuanced understanding of the fine-scale micrometeorological ) and phenological conditions (Wiesner et al 2019) that influence fuel moisture dynamics of both live and dead fuels (Jolly et al 2014;Kreye et al 2018). Changes over time represent a "fourth dimension" of fuels characterization.…”
Section: Fuels: Toward 3-and 4-dimensional Characterizationmentioning
confidence: 99%